PROBING SINGLE DNA MOLECULE TRANSPORT USING FABRICATED NANOPORES - Chen, Peng (2004)
Nanopores can serve as high throughput, single molecule sensing devices that provide insight into the distribution of static and dynamic molecular activities, properties, or interactions. We have studied double stranded DNA electrophoretic transport dynamics through fabricated nanopores in silicon nitride. A fabricated pore enables us to interrogate a broader range of molecules with a wider range of conditions than can be investigated in a self-assembled protein pore in a lipid membrane.